Evaluation of the Mineral Status of Two Ecosystems for Sustainable Goat Rearing in the Iberian Peninsula - David Vilallonga; Antonio Jiménez; Joaquín Sánchez; Santiago Andrés (Veterinary Medicine International, 2012)
The mineral status in two ecosystems typical of the Iberian Peninsula was evaluated. Ecosystem I was formed by forests and ecosystem II by hilly areas. The levels of calcium, phosphorus, magnesium, iron, copper, zinc and selenium in soils, rations and serum were measured. The concentratons of iron, copper, zinc and selenium were also checked in liver. Ecosystem I showed higher values of every mineral, except for phosphorus. Seasonal differences were recorded for rations and serum, with higher values in spring. The rations produced by both ecosystems met the mineral requirements of goats in lactation. Thus, both ecosystems are suitable for the development of an ecological goat farming system. However, extra supply of minerals, particularly calcium, may be needed in the maximum productions periods.